Lurking or listening? an ethnographic study of online and offline student political participation through the #MustFall protests at Rhodes University - Govender, Carissa Jade (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies, 2017)
The way media is created and consumed plays an important role in political participation as it provides information, guides thinking and allows citizens to make informed political choices. It can also interrogate the status quo and challenge existing systems or power relations. This thesis discusses the use of social media by Rhodes University students in the context of the 2015 #RhodesMustFall and #FeesMustFall protests in South Africa. This thesis interrogates the concept of slacktivism, a term used to describe online or digital activism which is considered to be less active and not as effective as physical activism. Furthermore, the thesis acknowledges that even when digital political participation is recognised, the emphasis and value is placed on those who speak and create content. The thesis examines the notion of participation and what counts as active citizenship. In particular, the majority of social media users who merely lurk and never contribute to content creation or online discussions are further investigated. The qualitative methodological approach used for this thesis involved three parts which looked at student activity on Facebook, student engagement offline, and how students made sense of their online and offline involvement. Firstly, a cyberethnographic investigation was done in order to understand the cyber world in which students are present. Thereafter, a participant observation was carried out to immerse myself in the offline spaces that students engaged in politically, to get a better sense of how their online presence influenced or supplemented their offline activity. Finally, individual interviews were carried out with lurkers to determine why they did not participate in traditional ways, both online and offline. The findings suggest that lurkers are in fact doing more than just being passively present. The high levels of attention paid to content posted by others on social media, as well as the way that the content influences their offline lives suggest that the choice to lurk is far more active than assumed. Students are consciously deciding to lurk for a multitude of reasons, one of which is for the opportunity to learn. Social media is a fast developing; increasingly used form of communication and how political communication across social media platforms is framed affects what we consider to be active engagement. By using theories of listening and emotion talk, the thesis provides new ways of understanding lurking by Rhodes University students on social media, which in turn can lead to better listening, better understanding and greater political participation.
Keywords: #Feesmustfall; #Rhodesmustfall; Social media -- Political aspects -- South Africa; Social movements -- South Africa; Political participation -- South Africa; Online social networks -- Political aspects -- South Africa; Student movements -- South Africa; Rhodes University -- Students